Observable plastic spin and comparison with other approaches - Huu Viem, Nguyen; Raniecki, B. (Archives of Mechanics, 1999)
The object of this paper is to formulate a relation for plastic spin, basing on the work of RANIECKI and MRÓZ [17] and the suggestion of HILL [5].